Donor human milk: the influence of processing technologies on its nutritional and microbial composition - Conboy-Stephenson, Ruth; Ross, R. Paul; Kelly, Alan L.; Stanton, Catherine (Frontiers in Nutrition, 2024)
Human milk is regarded as the gold standard nutrition for new-born infants, providing all nutrients required for adequate growth and development from birth to 6 months. In addition, human milk is host to an array of bioactive factors that confer immune protection to the new-born infant. For this reason, the supply of human milk is crucial for premature, seriously ill or low birth weight infants (<1500 g). When mother's own milk is unavailable, donor human milk is the recommended alternative by the World Health Organization. Prior to consumption, donor human milk undergoes pasteurization to ensure the eradication of bacterial agents and prevent the transfer of potentially pathogenic organisms. Currently, Holder Pasteurisation, a heat-based treatment, is the widely adopted pasteurization technique used by milk banks. Holder pasteurisation has demonstrated degradative effects on some of milk's biologically active factors, thus, depleting critical bioactive agents with known functional, protective and beneficial properties, ultimately reducing the immunoprotective value of donor human milk. As a result, alternative strategies for the processing of donor human milk have garnered much interest. These include thermal and non-thermal techniques. In the current review, we describe the effects of holder pasteurization and alternative milk processing technologies on milk's nutritional and bioactive properties. In addition, the capacity of each technique to ensure microbial inactivation of milk is summarized. These include the most extensively studied, High-Temperature Short-Time and High-Pressure Processing, the emerging yet promising techniques, microwave heating and UV-C irradiation and the lesser studied technologies, thermoultrasonication, retort processing, pulsed electric field and gamma irradiation. Herein, we collate the findings of studies to date, to allow for greater insight into the existing gaps in scientific knowledge. It is apparent that the lack of a cohesive standardized approach to human milk processing has resulted in contrasting findings, preventing a direct comparative analysis of the research. We conclude that donor human milk is a unique and valuable resource to the health sector, and although substantial research has been completed, persistent data disparities must be overcome to ensure optimal nutrition for the vulnerable new-born preterm infant group, in particular.